Geostrategi Indonesia di Indo-Pasifik: Antara hedging dan balancing di tengah persaingan Amerika Serikat-China - Najmuddin, Ahmad Ovan (Maliki Interdisciplinary Journal, 2026)
The rivalry between the United States (US) and China in the Indo-Pacific region has intensified since 2020 until 2026. This competition encompasses economic, military, and political influence in Southeast Asia. As the world’s largest archipelagic country, Indonesia holds a highly strategic geographical position because it controls vital trade routes such as the Strait of Malacca and the Natuna Sea.This article discusses Indonesia’s geostrategy amid the US-China rivalry. Indonesia tends to adopt a hedging strategy, which means not fully aligning with one major power. Indonesia seeks to build cooperation with various countries while maintaining the principle of its foreign policy, “bebas aktif” (independent and active).The analysis from the era of President Joko Widodo to President Prabowo Subianto shows that Indonesia’s hedging strategy has been quite successful in protecting national interests, particularly in the economic and security sectors. This can be seen from its support for the ASEAN Outlook on the Indo-Pacific (AOIP) and the diversification of cooperation with the US, China, Japan, and other countries. Nevertheless, this strategy still faces challenges such as pressure from both major powers and tensions in the South China Sea.